PENGEMBANGAN MODUL BERBASIS DISCOVERY LEARNING PADA MATERI JARINGAN TUMBUHAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA KELAS XI IPA SMA - Desi Ariana; Risya Pramana Situmorang; Agna Sulis Krave (Universitas Tanjungpura, 2020)
This study aims to develop a module based on discovery learning in improving scientific literacy skills in the 11th grade of science class in senior high school. This study refers to the modified Borg and Gall model into 7 steps, (1) preliminary study; (2) planning; (3) preparation of modules; (4) expert judgment; (5) revisions; (6) limited trials; (7) revision II. The research samples are in XI MIPA 2 and XI MIPA class at 3 SMAN 1 Bringin. The technique of collecting data using written tests, questionnaires, and observations. Hypothesis testing to measure the increase in cognitive learning outcomes of students using an independent t-test on n-gain students. Assessments from material experts, subject matter teachers, colleagues, and high school students show that the modules that have been developing suitable for use in the learning process with an achievement level of 86%, 95%, 88%, and 90% respectively. The results of the t-test showed an increase in students' literacy skills (p <0.05) of 0.71 (high category). It can be concluded, the modules that have been developing become worthy to use in the learning process and effective in enhancing the scientific literacy skills of senior high school students in XI class.AbstrakPenelitian ini bertujuan untuk mengembangkan modul berdasarkan discovery learning dalam meningkatkan keterampilan literasi sains di kelas XI MIPA di Sekolah Menengah Atas. Studi ini mengacu pada model Borg dan Gall yang dimodifikasi menjadi 7 langkah, (1) studi pendahuluan; (2) perencanaan; (3) persiapan modul; (4) penilaian ahli; (5) revisi; (6) uji coba terbatas; (7) revisi II. Sampel penelitian adalah kelas XI MIPA 2 dan XI MIPA di 3 SMAN 1 Bringin. Teknik pengumpulan data menggunakan tes tertulis, angket, dan observasi. Pengujian hipotesis untuk mengukur peningkatan hasil belajar kognitif siswa menggunakan uji-t independen pada siswa n-gain. Penilaian dari ahli materi, guru materi pelajaran, kolega, dan siswa sekolah menengah menunjukkan bahwa modul yang telah dikembangkan cocok untuk digunakan dalam proses pembelajaran dengan tingkat pencapaian masing-masing 86%, 95%, 88%, dan 90%. Hasil uji-t menunjukkan peningkatan keterampilan baca tulis siswa (p <0,05) dari 0,71 (kategori tinggi). Dapat disimpulkan, modul yang telah dikembangkan menjadi layak untuk digunakan dalam proses pembelajaran dan efektif dalam meningkatkan keterampilan literasi ilmiah siswa SMA di kelas XI.Kata Kunci: discovery learning, modul, uji jaringan tumbuhan